2022
DOI: 10.3389/fbioe.2022.831300
|View full text |Cite
|
Sign up to set email alerts
|

Decellularization Strategies for Regenerating Cardiac and Skeletal Muscle Tissues

Abstract: Cardiovascular disease is the leading cause of death worldwide and is associated with approximately 17.9 million deaths each year. Musculoskeletal conditions affect more than 1.71 billion people globally and are the leading cause of disability. These two areas represent a massive global health burden that is perpetuated by a lack of functionally restorative treatment options. The fields of regenerative medicine and tissue engineering offer great promise for the development of therapies to repair damaged or dis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
19
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(19 citation statements)
references
References 114 publications
(252 reference statements)
0
19
0
Order By: Relevance
“…The immune response is mainly directed against the proteins and lipids of cell membranes; thus, cell extraction from tissue is a promising method to avoid the creation of a post-transplant immune response in the body of the recipient [ 4 , 12 , 13 , 14 , 15 , 16 ]. The removal of cellular components should minimize the immunologically induced inflammatory process, which may weaken the biodegradation process of the transplanted bioprosthesis [ 15 ].…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The immune response is mainly directed against the proteins and lipids of cell membranes; thus, cell extraction from tissue is a promising method to avoid the creation of a post-transplant immune response in the body of the recipient [ 4 , 12 , 13 , 14 , 15 , 16 ]. The removal of cellular components should minimize the immunologically induced inflammatory process, which may weaken the biodegradation process of the transplanted bioprosthesis [ 15 ].…”
Section: Resultsmentioning
confidence: 99%
“…The procedure of removing cells from allogeneic human dermis results in a cell-free, non-immunogenic matrix composed of extracellular matrix (ECM) elements that can be re-inhabited by autologous cells. Such cell-free dermal matrices (ADMs) can also stimulate natural regenerative and reconstructive mechanisms [ 12 , 13 , 14 , 15 , 16 , 17 , 18 , 19 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Generation of acellular myoscaffolds using chemical decellularization. For more than a decade, decellularized scaffolds have been generated from heart and muscle and studied for their ability to support cellular regeneration (reviewed in (Tan et al, 2022)). Recently Stearns-Reider et al published an "on-slide" decellularization method using 30µm tissue sections exposed to 1% SDS for 40 mins to generate dECM myoscaffolds (Stearns-Reider et al, 2022).…”
Section: Resultsmentioning
confidence: 99%
“…This enzyme is used in many decellularization protocols targeting the C-side bonds in lysine and arginine amino acids but disrupting the tissue microstructure when applied for too long. Trypsin is mainly used with detergents or enzymatic chelating agents (e.g., ethylenediaminetetraacetic acid—EDTA) [ 93 , 95 , 96 ]. A study published in 2013 by Merna et al demonstrated that decellularization of whole porcine hearts using trypsin significantly decreased DNA while severely reducing the structure and mechanical integrity of the ECM [ 79 ].…”
Section: Ecm Decellularization Methodsmentioning
confidence: 99%